Pengaruh Nilai Religiosity dan Product Knowledge Terhadap Minat Beli Produk Fashion Ladyfame Dalam Perspektif Bisnis Islam : Studi Pada Konsumen Ladyfame Bandar Lampung - Fatih Fuadi; Heni Verawati; Nadiya Putri Ananda Anom (Journal of Islamic Economics and Finance, 2024)
The large number of businesses currently developing shows that economic transactions are increasingly developing. People's needs for fashion and clothing have developed very rapidly and have advanced following world fashion trends, so that many people want to follow developments and dress styles according to the latest trends. Currently, fashion products are one of human clothing needs, so many people are interested in the fashion models that people want. Fashion will continue to change from time to time following increasingly advanced and modern developments. Every year, even every generation, has a different fashion character. However, the development of fashion which continues to advance and develop will always be something interesting to watch or follow according to existing trends because through clothes we can find out many things about people's lives at that time. The formulation of the problem in this research is: Does the value of religiosity influence the interest in buying Ladyfame fashion products, Does product knowledge influence the interest in buying Ladyfame fashion products, Does the value of religiosity and product knowledge influence the interest in buying Ladyfame fashion products, and what is the value of religiosity, product knowledge and purchasing interest in an Islamic business perspective. This research aims to analyze the influence of religiosity values, product knowledge on intention to purchase Ladyfame fashion products and from an Islamic business perspective. This study used quantitative methods. The sample size of 100 Ladyfame consumer respondents is determined the Lemeshow formula. The data analysis method in this research uses SPSS 23. The tests used in this research are validity tests, reliability tests, and hypothesis tests.The results of this study show that the value of religiosity has no significant influence on interest in purchasing Ladyfame fashion products. Product knowledge has a significant influence on interest in purchasing Ladyfame fashion products. And the values ​​of religiosity and product knowledge influence the interest in buying Ladyfame fashion products. Viewed from an Islamic business perspective, the value of religiosity towards buying interest must be in accordance with the values ​​stated in the law of buying and selling which are summarized in the pillars of Bai' As-Salam, namely the existence of sellers and buyers, the existence of goods and money, the existence of sigat (ijab qabul) or contract that has been agreed to by both parties. Meanwhile, product knowledge is also really needed in purchasing activities so that you don't waste your buying interest because Allah really doesn't like people who are wasteful or wasteful. Having Product Knowledge or knowledge about a product means consumers don't spend excessively, because when consumers already know about a product and are interested in buying that product will be more interested in a product that they already know about, so they will be interested in buying a product according to their needs.